2017
DOI: 10.1111/ejh.12909
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary disease at diagnosis of AML does not influence outcome of patients undergoing allogeneic hematopoietic cell transplant in CR1

Abstract: We conclude that EMD at diagnosis of AML does not seem to influence outcomes following allo-HCT performed in CR1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Indeed, CNS seems to be the most common extramedullary involvement site in most clinical studies in ALL patients [7]. Regarding risk factors for EMR, studies of AML patients reported that extramedullary involvement before transplantation had no impact on outcome [20,21], similar to our large study in both AML and ALL. Despite the reportedly higher incidence of EMR in ALL compared with AML [7À10], our study did not confirm this finding.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, CNS seems to be the most common extramedullary involvement site in most clinical studies in ALL patients [7]. Regarding risk factors for EMR, studies of AML patients reported that extramedullary involvement before transplantation had no impact on outcome [20,21], similar to our large study in both AML and ALL. Despite the reportedly higher incidence of EMR in ALL compared with AML [7À10], our study did not confirm this finding.…”
Section: Discussionsupporting
confidence: 85%
“…A previous study from our center, which looked at 303 consecutive AML transplants in CR1, reported on 39 patients (13%) with evidence of extramedullary AML prior to transplant (of these, 16 patients [5.2%] had CNS‐AML), and there was no effect of extramedullary involvement on survival. This earlier study did not specifically look at the effect of CNS‐AML on transplant outcomes, which is the focus of the current study in a larger and more recent cohort of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Extramedullary involvement (EMI) refers to leukemic cells found in organs or tissue outside the blood or bone marrow. 1 The most common sites of extramedullary disease are skin, bone, and lymph nodes. 2 Although the exact frequency is unknown, EMI has been estimated to occur in 3–8% of adult patients with acute myeloid leukemia (AML), and it can be diagnosed in concomitance, following or antedating the onset of the bone marrow involvement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, others report that EMI is not an independent indicator of a worse prognosis than medullar disease alone. 1 This study retrospectively analyzes the incidence, risk factors, treatment outcomes, and overall prognosis in a cohort of adult patients with AML with EMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation